Use of T1ρMR imaging in Sjögren's syndrome with normal appearing parotid glands: Initial findings. Issue 4 (11th October 2016) - Chu, Chen; Zhou, Nan; Zhang, Huayong; Dou, Xin; Li, Ming; Liu, Song; Zhu, Yun; Chen, Weibo; Chan, Queenie; He, Jian; Sun, Lingyun; Zhou, Zhengyang
Abstract : Purpose: To explore the feasibility of parotid spin‐lattice relaxation time in the rotating frame (T1ρ) MR imaging in the diagnosis of Sjögren's syndrome (SS) without morphological changes of the parotid glands. Materials and Methods: The study enrolled 32 consecutive SS patients without morphological changes of parotid glands and 32 age‐ and gender‐matched healthy volunteers who underwent parotid 3.0 Tesla MR imaging, including T1ρ sequences. Follow‐up imaging was performed at 3 months. T1 signal intensities and T1ρ values of bilateral parotid glands were compared using paired samples t‐test. Parotid T1 signal intensities and T1ρ values were compared using two independent samples t‐test. Diagnostic performance of the parotid T1ρ values was evaluated by receiver operating characteristic analysis. The intraclass correlation coefficient (ICC) was calculated to evaluate the reproducibility of parotid T1ρ measurements. Results: There were no significant differences of T1 signal intensities and T1ρ values between bilateral parotid glands in SS patients and healthy volunteers ( P = 0.170, 0.886 and 0.942, 0.229). The parotid T1ρ values of SS patients (96.47 ± 15.38 ms) were significantly higher than those of healthy volunteers (84.25 ± 6.11 ms) ( P < 0.001), while there were no significant differences of T1 signal intensities between SS patients and healthy volunteers ( P = 0.655). With a cutoff value of 88.02 ms, the sensitivity and specificity of the parotid T1ρ value was 75.0% and 100.0% in the diagnosis of SS. The reproducibility of parotid T1ρ measurement was excellent (ICC: 0.934−0.995). Conclusion: Parotid T1ρ MR imaging held a potential role in diagnosing SS without morphological changes of parotid glands. Level of Evidence: 2 J. Magn. Reson. Imaging 2017;45:1005–1012